The Effects of Role Conflict and Emotional Exhaustion on Organizational Citizenship Behavior (OCB), With Affective Commitment as An Intervening Variable - Raymond Raymond; Mohamad Gita Indrawan; Angelina Eleonora Rumengan (Advances in Human Resource Management Research, 2026)
Abstract Purpose: This study aims to examine the effects of role conflict and emotional exhaustion on Organizational Citizenship Behavior (OCB), with affective commitment as an intervening variable among lecturers at private universities in City of Batam. Research Method: Quantitative research approach was employed using survey method. Data were collected through structured questionnaires measured on Likert scale. The sample consisted of lecturers from private universities in City of Batam, selected using sampling technique aligned with the characteristics of population. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that role conflict has positive and significant effect on OCB, suggesting that role-related pressures in academic environment might encourage lecturers to exhibit extra-role behaviors as form of professional adaptation. In contrast, emotional exhaustion has negative and significant effect on OCB, indicating that depletion of emotional resources reduces lecturers’ willingness to engage in voluntary behaviors beyond their formal duties. Furthermore, emotional exhaustion has negative and significant effect on affective commitment,   Results and Discussion: The role conflict does not significantly influence affective commitment. Affective commitment is found to have positive and significant effect on OCB and serves as significant mediating variable in relationship between emotional exhaustion and OCB. However, affective commitment does not mediate relationship between role conflict and OCB. Implications: These findings contribute to development of organizational behavior literature, particularly in higher education context and provide practical implications for university management in formulating human resource policies aimed at strengthening lecturers’ affective commitment and managing emotional exhaustion to enhance OCB. Originality: This study extends the OCB literature by simultaneously examining role conflict and emotional exhaustion through the mediating role of affective commitment in the context of private higher education institutions in Indonesia, a setting that remains underexplored in prior research.